PENGARUH MODEL PROBLEM BASED LEARNING (PBL) PADA PEMBELAJARAN MATEMATIKA SISWA SEKOLAH DASAR : STUDI META-ANALISIS - Fatkhul Arifin; Tri Anjani Ashari; Fauzan Fauzan (Muallimuna : Jurnal Madrasah Ibtidaiyah, 2021)
This study aims to determine the influence of the Problem Based Learning (PBL) learning model on the overall mathematics learning in several scientific journals at the basic education level "at the basic education level. The method used is meta-analysis, namely a descriptive narrative review or systematic review by analyzing the results. The results of research that have been published nationally relating to the influence of the Problem Based Learning (PBL) learning model on elementary school students' mathematics learning The sample in this study is a random sampling technique with a total of thirteen journal articles that have been published nationally in Indonesia with a span of years. 2014-2020 at the basic education level which discusses the writing of experiments on the effect of the Problem Based Learning (PBL) learning model in elementary school students' Mathematics learning. The instrument used is a coding data sheet that summarizes the data. and journal information. Based on the analysis of the overall effect value, the average value of the influence is 0.416, which means that it is in the large effect category. The findings of the analysis also show that the problem-based learning model has an influence on Mathematics learning in basic education. This shows the conclusion that the-pl problem based learning model is more effective in learning mathematics compared to the conventional learning model in this study